(untitled) (Research Journal Tahqeeqat, 2025)
In Urdu Novel, women have presented in various themes and shades. Most of which, they have depicted the status of women in society and the problems of their personal and social lives. Khalida Hussain is a renowned Urdu fiction writer. In Kaaghzi Ghaat, she has depicted the social situation of women in a traditional environment in the contemporary era. Kaaghzi Ghaat, the novel presents the social status of a Pakistani educated woman who grew up after the establishment of Pakistan and her attempt to break unwanted social norms. This article describes the efforts of middle-class Pakistani women of different ages to identify themselves.